Prototype of blood sugar measuring instrument with non invasive method using near infrared - Saraswati, Irma; Dzaky, Muhammad Fikri; Haryanto, Heri (Jurnal Teknika, 2024)
At present the measurement of blood sugar still uses an invasive tool, this disrupts the patient's comfort and can cause infection and pain. So that a non-invasive tool is needed to measure blood sugar. Tool testing was done by measuring blood sugar levels in 35 patients and seeing a correlation between the value of blood sugar levels with ADC. The test results showed that the value of changes in blood sugar levels followed y = -0.146x + 164.89 Coefficient value R = 0.9233 The value of the accuracy of the tool was 91.086% and the precision of 94.3026%. Blood sugar measuring devices that have been designed to monitor the blood sugar of users by using the internet. This blood sugar meter cannot be used as a reference for the actual blood sugar level. However, the realization of this tool can still determine a rough estimate of the high and low levels of sugar in the blood.